(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The problem of limited fresh water sources has worldwide ramifications. Rising global demandis the single most important contributor to the rapid and severe decline of the world’s freshwater supplies.As a result of this problem, the scientists were inspired to develop novel and inexpensive approaches tofixing it. In order to make wastewater from industrial operations suitable for use in agriculture, manysolutions have been proposed, one of which is the removal of dangerous pollutants. This article shedslight on both traditional and contemporary approaches utilised for this function, with special focus onthe recycling of waste products and the utilisation of renewable materials derived from naturalresources. The article also zeroes attention on a minor but growing development in the industry the useof polymer nanocomposites in the purification of water. Nanocomposites made from polymers found innature are called polymer nanocomposites.